Design, implementation and evaluation of value-based payment models: a Delphi study - Diogo L. L. Leao; Lise A. M. Moers; Henricus-Paul Cremers; Dennis van Veghel; Wim Groot; Milena Pavlova (BMC Health Services Research, 2025)
Abstract Background This study explores the facilitating and inhibiting factors in the design/development, implementation, and applicability/evaluation of value-based payment models of integrated care. The Delphi technique was used to reach consensus among a panel of (inter)national experts on these factors. Methods An expert panel of 15 members participated in a three-round Delphi study. Factors from experts and literature were used to compile a list of 40 facilitators and 40 inhibitors. Afterwards, experts were asked to rate the importance of these factors using a 5-point Likert scale. Results Eight facilitating (e.g., transparency, communication, and trust among involved stakeholders) and seven inhibiting factors (e.g., lack of motivation and engagement among involved stakeholders) achieved full consensus. Timely availability of data and an integrated information technology system for data registration (a facilitator) were the only factors achieving full consensus through a very high agreement. Conclusions Adequate outcome measures, targets, benchmarks, and incentives are important in value-based payment models. The less quantifiable items, such as strong leadership, transparency, communication and trust, and motivation and engagement of the involved stakeholders, are also important for successful adoption of these models and promote high-quality care at lower or equal costs.